How Do Tides and Tsunamis Interact in a Highly Energetic Channel? The Case of Canal Chacao, Chile. Issue 12 (8th December 2017) - Winckler, Patricio; Sepúlveda, Ignacio; Aron, Felipe; Contreras‐López, Manuel
Abstract: This study aims at understanding the role of tidal level, speed, and direction in tsunami propagation in highly energetic tidal channels. The main goal is to comprehend whether tide‐tsunami interactions enhance/reduce elevation, currents speeds, and arrival times, when compared to pure tsunami models and to simulations in which tides and tsunamis are linearly superimposed. We designed various numerical experiments to compute the tsunami propagation along Canal Chacao, a highly energetic channel in the Chilean Patagonia lying on a subduction margin prone to megathrust earthquakes. Three modeling approaches were implemented under the same seismic scenario: a tsunami model with a constant tide level, a series of six composite models in which independent tide and tsunami simulations are linearly superimposed, and a series of six tide‐tsunami nonlinear interaction models ( full models ). We found that hydrodynamic patterns differ significantly among approaches, being the composite and full models sensitive to both the tidal phase at which the tsunami is triggered and the local depth of the channel. When compared to full models, composite models adequately predicted the maximum surface elevation, but largely overestimated currents. The amplitude and arrival time of the tsunami‐leading wave computed with the full model was found to be strongly dependent on the direction of the tidal current and less responsive to the tide level and the tidal current speed. These outcomes emphasize the importance of addressing more carefully the interactions of tides and tsunamis on hazard assessment studies. Key Points: Nonlinear tide‐tsunami interactions triggered by advection and friction are relevant in regions with high tidal speeds and shallow depths Linear superposition of tide and tsunami adequately predicts the maximum surface elevation, but largely overestimates currents Arrival time and elevation of leading waves are strongly affected by the tidal flow direction and less influenced by its level and speed